PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI PADA PESERTA DIDIK KELAS XI - Ridwan Alwi Fauzi; Wikanengsih Wikanengsih (IKIP Siliwangi, 2019)
In this study discusses learning to write explanatory texts. This research the author wants to try to apply a project-based learning model in learning to write explanatory texts that are expected to improve the ability of students in writing explanatory texts. This study aims to determine the comparison of student learning outcomes between those who use project-based learning models with those who use conventional learning. The research subject is class XI. The method used in this study uses quasi-experimental and nonequivalent control group design. The instrument in this study used test questions. The sample consisted of the experimental class (using project-based learning) and the control class (using conventional learning), then the sample was classified according to its achievement in three categories: students with high (T), medium (S), and low (R) explanatory text ). The research subjects consisted of 30 students each who had the same initial ability. The results of this study showed the average posttest of students in the experimental class was 71.38, while in the control class the average posettest of students was 66.61. It can be concluded that a significant increase in the ability to write explanatory texts can be done by applying a project-based learning model.